Reducing same-day cancellations of precious CT simulation slots: A quality improvement project. Issue 28 (1st October 2022) - Ng, Ivy; Lai, Michelle; Ng, Jessie; Beltran, Richerlyn Quindara; Teng, Kie Yin; Wei, Wei; Lee, Chia Ching; Pastores, Kathleen Viloria; Chiau, Ye Lin; Chuah, Jyy Yin; Leong, Cheng Nang; Poon, Keah How; et al.
Abstract : 301 Background: CT simulation (CTsim) is a prerequisite step in radiotherapy treatment. Each successfully completed CTsim brings a patient a step closer to receiving their radiotherapy. A non-attempt or unsuccessful attempt (both reflected as cancellations) also delays radiotherapy for another patient. Baseline data revealed that 33% of CTsim appointments were cancelled, of which 47% occurred on the same day. Cancellations made on the same day provides little reaction time for slots to be allocated to another patient and leads to inefficiency in resource utilisation. This project aims to reduce the cancellations occurring on the same day from 15.5% to 10% within 6 months at National University Cancer Institute radiotherapy center at Tan Tock Seng Hospital. Methods: A cause-and-effect diagram was constructed to identify reasons attributing to existing same-day cancellations. Multi-voting and Pareto analysis were conducted to identify 3 main root causes. Interventions were introduced and then tested using the Plan-Do-Study-Act approach. Run chart was used to monitor the proportion of same-day cancellations over the total number of CTsim appointments. Results: Three root causes identified were 1) no workflow to check on patient's adequacy of preparation leading up to CTsim 2) no workflow to identify potential non-attendance 3) no take-home information detailing CTsim process. Interventions introduced included establishing workflow to assess adequacy of patients' preparation required for successful CTsim and integrating a screening phone call to confirm patient's attendance two days prior to CTsim appointment day and handing out information sheet detailing instructions for CTsim respectively. We achieved our target in our fourth month and sustained the results for 2 further months. Mean was 5% in the last three months. This reduction of same-day cancellation improves efficiency in resource utilisation and reduces delay in access to radiotherapy. Conclusions: Using quality improvement tools, we have successfully reduced the same-day cancellations of our precious CT simulation slots from 15.5% to 5%.